2020
DOI: 10.1016/j.isci.2020.101459
|View full text |Cite
|
Sign up to set email alerts
|

The Guaymas Basin Subseafloor Sedimentary Archaeome Reflects Complex Environmental Histories

Abstract: Summary We explore archaeal distributions in sedimentary subseafloor habitats of Guaymas Basin and the adjacent Sonora Margin, located in the Gulf of California, México. Sampling locations include (1) control sediments without hydrothermal or seep influence, (2) Sonora Margin sediments underlying oxygen minimum zone water, (3) compacted, highly reduced sediments from a pressure ridge with numerous seeps at the base of the Sonora Margin, and (4) sediments impacted by hydrothermal circulation at the o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 55 publications
1
23
0
Order By: Relevance
“…In contrast to high-throughput sequencing approaches that yield 10 4 to 10 5 sequences per sample (see Teske et al, 2019 andRamírez et al, 2020 for recent Guaymas Basin examples), the spatial resolution of DGGE gels limits amplicon separation and identification to approximately a few dozen phylotypes, which are visually tracked in different sampling layers and sediment depths. In addition to the difference in sequence yield and diversity, we note that microbial depth resolution in 2-millimeter depth intervals comes with its own inherent limitations.…”
Section: Methodological Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to high-throughput sequencing approaches that yield 10 4 to 10 5 sequences per sample (see Teske et al, 2019 andRamírez et al, 2020 for recent Guaymas Basin examples), the spatial resolution of DGGE gels limits amplicon separation and identification to approximately a few dozen phylotypes, which are visually tracked in different sampling layers and sediment depths. In addition to the difference in sequence yield and diversity, we note that microbial depth resolution in 2-millimeter depth intervals comes with its own inherent limitations.…”
Section: Methodological Limitationsmentioning
confidence: 99%
“…Essentially a molecular fingerprinting method, DGGE separates PCR amplicons into different phylotypes with distinct migration patterns in denaturing gels that can be visually matched side by side, and probed or excised and sequenced for closer identification (Muyzer and Smalla, 1998;Strathdee and Free, 2013). The sequence yield and diversity spectrum of DGGE bands is not at all comparable with high-throughput sequencing surveys (for Guaymas Basin examples, see Biddle et al, 2012;Cruaud et al, 2015;Dowell et al, 2016;Teske et al, 2019Teske et al, , 2021Ramírez et al, 2020), but still gives an overview on the most abundant community members. The visual comparison of community patterns allows targeted sequencing of DGGE bands that reflect the differences between the investigated samples.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to previous small-scale surveys that focused on individual hydrothermal mounds or microbial mats (McKay et al, 2012(McKay et al, , 2016Dowell et al, 2016), the sampling sites are separated by distances of hundreds of meters or several miles (Figure 1). Within a few miles of each other, the greater Guaymas Basin geo-ecosystem includes hydrothermal areas at the southern Guaymas Basin spreading center (Teske et al, 2016), off-axis hydrothermal sites (Teske et al, 2019;Ramírez et al, 2020), hydrothermal mounds just off the northern spreading center (Berndt et al, 2016), and cold seeps on the northern flanking regions and the adjacent Sonora Margin (Geilert et al, 2018). Methane-rich off-axis cold seeps have been documented by deep-tow photography of faunal communities and carbonates, and by in situ measurements of methane anomalies in the deep water column (Lizarralde et al, 2011), and some cold seep sites have been sampled further by multicoring and gravity coring of sediments and dredging of seafloor minerals (Geilert et al, 2018;Núñez-Useche et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…To explore environmental controls on fungal diversity and occurrence patterns, and fungal associations with bacteria and archaea, we analyzed site- and depth-related patterns of bacteria, archaea and fungi in hydrothermally influenced sediments of Guaymas Basin under different thermal and geochemical regimes retrieved from four different locations: i) hot hydrothermal sediments covered by orange-pigmented Beggiatoaceae mats in the Cathedral Hill area, ii) temperate sediments covered by yellow sulfur precipitates and filamentous sulfur oxidizers at the Aceto Balsamico location [ 2 ], iii) hot sediments with orange-pigmented mats surrounded by yellow and white mats at the Marker 14 location [ 14 ], and iv) bare background sediments with ambient seawater temperatures at a nearby control site ( Fig 1 , S1 Fig in S1 File ). Previous investigations in Guaymas Basin have shown that sediment temperature affects Beggiatoa mat heterogeneity [ 9 ], limits methane and short-chain alkane oxidation and organic matter remineralization in hydrothermal sediments [ 14 , 15 ] and cold seeps [ 28 ]; further, site-specific environmental histories can influence ecological structuring [ 29 ]. Overall, these studies suggest that bacterial and archaeal communities are predominantly structured by in-situ thermal and geochemical regimes.…”
Section: Introductionmentioning
confidence: 99%